Denmark : Financial Sector Assessment Program-Technical Note-Competition in the Banking Sector. (IMF Staff Country Reports; Country Report ;, 2007)
This technical note analyzes the competition in the banking sector in Denmark. It reveals that Denmark has a fairly competitive and efficient banking sector. Measured by various indicators, efficiency of banking intermediation has been improving in recent years. The banking sector has become concentrated, and profitability of banks is relatively high and growing. The Danish Bankers Association and the Danish Consumers Association, in collaboration with the Danish Financial Supervisory Authority, should continue efforts to promote the transparency of pricing and quality of different products and services offered by banks.